2012
DOI: 10.7314/apjcp.2012.13.4.1365
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Promotes the Synthesis of Pro-IL-1β and Pro-IL-18 by Activation of p38 MAPK and NF-κB Through Receptors for Advanced Glycation End-products in Macrophages

Abstract: The high mobility group box-1 (HMGB1) protein and NALP3 inflammasome have been identified to play important roles in inflammation and cancer pathogenesis, but the relationships between the two and cancer remain unclear. The current study investigated the relationship between HMGB1 and the NALP3 inflammasome in THP-1 macrophages. HMGB1 was found unable to activate the NALP3 inflammasome and failed to induce the release of the IL-1β and IL-18 in THP-1 macrophages. HMGB1 was also found significantly enhanced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 20 publications
0
76
0
Order By: Relevance
“…In the nucleus, HMGB1 functions as a non-histone nucleosomal protein that binds DNA, contributes to stabilization of nucleosomes, and promotes DNA repair and replication (Bustin, 1999). In the extracellular milieu, HMGB1 is a pro-inflammatory cytokine that acts as an alarmin via passive release from damaged or necrotic cells (Beyer et al, 2012;He et al, 2012;Yi et al, 2013) or by active secretion from innate immune system cells in response to LPS, TNF-a or IL-1β stimulation to induce T-cell activation, cytokine production, and inflammatory responses by the transduction of cellular signals through its receptors (Akirav et al, 2012;Kang et al, 2013;Mohammad et al, 2013). Aside from these pro-inflammatory functions, HMGB1 protein also promotes regeneration processes and accelerates cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%
“…In the nucleus, HMGB1 functions as a non-histone nucleosomal protein that binds DNA, contributes to stabilization of nucleosomes, and promotes DNA repair and replication (Bustin, 1999). In the extracellular milieu, HMGB1 is a pro-inflammatory cytokine that acts as an alarmin via passive release from damaged or necrotic cells (Beyer et al, 2012;He et al, 2012;Yi et al, 2013) or by active secretion from innate immune system cells in response to LPS, TNF-a or IL-1β stimulation to induce T-cell activation, cytokine production, and inflammatory responses by the transduction of cellular signals through its receptors (Akirav et al, 2012;Kang et al, 2013;Mohammad et al, 2013). Aside from these pro-inflammatory functions, HMGB1 protein also promotes regeneration processes and accelerates cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%
“…Certain results suggested that high mobility group box-1 administration stimulates pro-IL-18 synthesis via NF-κB and p38 MAPK in THP-1 macrophages, while LPS-stimulation does not induce the expression of pro-IL-18 mRNA and protein in human primary peripheral blood mononuclear cells (7,27).…”
Section: Introductionmentioning
confidence: 99%
“…Cytokine patterns (increase in IL8, IL18, and MCP1 compared to vehicle control) reflected an immunomodulation in THP-1 cells cultured in tumor cell supernatants as well. IL18 is marker of inflammasome activation in THP-1 cells [48], while lipopolysaccharide-stimulated THP-1 monocytes secrete IL8 [49] and MCP1 [50]. IL8 is also released in response to oxidative stimuli [51].…”
Section: Discussionmentioning
confidence: 99%